Sistem Informasi Penjualan Sparepart Dan Service Mobil Pada Bengkel Java Auto Service Berbasis Web - Gafar Ilyaz JP; Juli Hati Fitri; Syaiful Zuhri Harahap (Universitas Labuhanbatu, 2021)
Java Auto Service repairis a business engaged in the sale of spare parts and service Services. In the Java Auto Service Workshop the process of recording and processing spare parts data, the amount, price of spare parts and sales transaction data, as well as service service transaction data is still done by hand writing. To overcome these problems, a web-based system is needed as one of the solutions. For this reason, it is necessary to optimize the use of computers to data processing by designing an information system that is applied to the PHP programming language and mySQL data in order to solve existing problems and be able to answer the needs of the company.The purpose of this study was made to facilitate the owner of the workshop in processing spare parts sales data, service data, sparepart data reports as well as the creation of sales and service transaction notes become faster and more efficient so that it can help increase the profits of the Java Auto Service workshop in running its business.